Local Wisdom of Lombok Community in the Development of Tourism Law: A Study in the Kuta Mandalika Special Economic Zone - Yulias Erwin (Faculty of Law, Universitas Pekalongan, 2025)
The rapid development of global tourism involves various social aspects, including the local wisdom of a nation. In tourism, local wisdom holds a dual role: on one hand, it adds cultural depth and uniqueness to tourism promotion; on the other, it faces the threat of degradation due to the influence of Western values brought by foreign tourists. This study investigates the role of local wisdom in the development of tourism law in Lombok, a region designated as a National Strategic Project in tourism. The research was conducted in the Kuta Mandalika Special Economic Zone, Central Lombok, and analyzed using a normative-empirical approach. The results showed that local wisdom can significantly influence tourism law, particularly in legal substance, structure, legal culture, and dispute resolution mechanisms. Implementing tourism law development policies based on local wisdom can help preserve tourism assets, transform local wisdom into regional regulations, resolve disputes, and improve tourism safety and order. This research is expected to contribute significantly to future legal frameworks, underscoring the importance of integrating local knowledge into formal legal systems, ensuring cultural heritage preservation and sustainable tourism advancement.